The effect of tropical weathering on the strength and anisotropy index of weathered shale - Maiye, Olumorin Michael (2014)
Sedimentary rocks to be specific shale as it is the rock being studied can be adversely affected by weathering action; hence the alteration of its engineering properties is incontestable. The manipulation of the engineering properties of shale becomes more significant as it possesses fine lamination structures which tend to split unevenly, parallel to the weakness plane. It becomes so severe when the rock material is subjected to structural loads, slope cut and higher weathering process in tropical region. This study focus on the effect of weathering on the strength, and anisotropy index Ia(50) of shale of fresh to highly weathered (grades I–IV) shale collected at Nusajaya,west of Johor Baharu, Malaysia. A total of 96 samples representing various weathering grades were collected from the field and tested using 24 samples for each different weathering grade at varying moisture by immersing them in water at different duration of time ranging from 15, 30 and 60 minutes. Point load tests for the determination of the strength index Is(50) of the rock were measured at 0o and 90o orientations. For weathered shale (grade I to IV), the mean initial moisture content ranges from 0.12% to 10.69 respectively, while the initial mean strength index has maximum of 7.78 MPa and 0.4 MPa respectively. The results revealed that there is a significant relationship among weathering grades, moisture absorption, strength and anisotropy index of shale. The moisture absorption is dependent on the amount of clay minerals present in the rock material which indirectly affects the strength. In addition, the result shows a unique pattern on the range of anisotropy index for various weathering grades. In conclusion,this study also indicates that shale with higher moisture content and increase in weathering grade exhibits wider range of anisotropy index with lower strength values